Prognostic Factors for IVF Success: Diagnostic Testing and Evidence-Based Interventions - Papathanasiou, Athanasios; Bhattacharya, Siladitya (Seminars in Reproductive Medicine, 2015)
Numerous tests and interventions have been proposed for optimizing performance in preparation for in vitro fertilization (IVF) treatment. We critically appraised the available evidence underpinning some of the popular investigations and treatments, including the role of hysteroscopy, laparoscopy, ovarian reserve tests, sperm function tests, as well as the role of lifestyle modifications or surgery for endometriosis, fibroids, and endometrial polyps. We also reviewed the evidence behind novel techniques, such as the use of endometrial injury before IVF. Only a few of the aforementioned modalities are justified based on the available research evidence. Other factors may affect the uptake of a test or intervention before IVF, namely the complexity of the proposed modality, its potential for harm, and its cost-effectiveness.
Keywords: IVF; tests; interventions; success; evidence-based